2020
DOI: 10.1021/acsaem.0c00076
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence of Less Charge Accumulation in Highly Durable Polymer Solar Cells Using Operando Electron Spin Resonance Spectroscopy

Abstract: Inverted-type polymer solar cells with poly[naphtho [1,2-c:5,6-c']bis [1,2,5]thiadiazole-5,10diyl [3,4'-bis(2-butyloctyl)[2,2'-bithiophene]-5,5'-diyl]thiazolo [5,4-d]thiazole-2,5-diyl[3',4-bis (2-butyloctyl)[2,2'-bithiophene]-5,5'-diyl]] (PTzNTz) have attracted attention because of its high power conversion efficiency and thermal stability. However, the internal deterioration mechanism hasn't yet been completely clarified. Here, we report operand electron spin resonance (ESR) spectroscopy of the highly durab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…The measured temperatures were between 4 K and room temperature. The parts of the above-mentioned ESR spectroscopy characterization method have been described in the previous works [22][23][24][25][26]37,38,43 .…”
Section: Methodsmentioning
confidence: 99%
“…The measured temperatures were between 4 K and room temperature. The parts of the above-mentioned ESR spectroscopy characterization method have been described in the previous works [22][23][24][25][26]37,38,43 .…”
Section: Methodsmentioning
confidence: 99%
“…It is very interesting to investigate the charge accumulation in PTzNTz polymer solar cells. In our previous studies, the signals of PTzNTz solar cells have been identified as a hole signal of PTzNTz and an electron signal of PC 71 BM under simulated solar irradiation [23]. We also have found that the ESR intensity of the PTzNTz cell with a hole transport layer (HTL) of WO x is smaller than that with MoO x HTL.…”
Section: Introductionmentioning
confidence: 94%
“…We used the continuous-wave ESR method in the experiments which performs a lockin detection with an external magnetic field (H) modulation of 100 kHz. Thus, photogenerated charges with a lifetime (<10 μs) cannot be observed, and it is possible to observe only long-lived (or accumulated) photogenerated charges with an unpaired spin with a long lifetime (>10 μs) in thin films and solar cells [23][24][25][26].…”
Section: Esr Measurementsmentioning
confidence: 99%
See 2 more Smart Citations